1999
DOI: 10.1097/00005537-199911000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Obstruction: An Alternative to Ostiomeatal Complex Dysfunction in Sinus Disease

Abstract: We have established independent models of nasal obstruction and ostial occlusion in the same animal. Our findings suggest that ostiomeatal complex dysfunction might not be the sole underlying factor in the pathogenesis of sinus disease in all individuals. Integrity of nasal airflow seems to have a significant effect on the maintenance of the aerobic antral environment, essential to the maintenance of normal sinus function. Modulation of maxillary sinus gas composition by nasal airflow, independent of ostial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…3,5 A recent animal study suggested that mere nasal obstruction without ostial occlusion plays an important role in the pathogenesis of sinus disease. 6 Computed tomography (CT) scans of adults with an early stage of common cold have demonstrated extensive pathological changes in the paranasal sinuses, indicating impaired sinus drainage and ventilation, which may increase the risk of bacterial sinusitis. 7 We have earlier shown that subjects with allergic rhinitis and susceptibility to recurrent sinusitis have impaired sinus functioning during viral colds.…”
mentioning
confidence: 99%
“…3,5 A recent animal study suggested that mere nasal obstruction without ostial occlusion plays an important role in the pathogenesis of sinus disease. 6 Computed tomography (CT) scans of adults with an early stage of common cold have demonstrated extensive pathological changes in the paranasal sinuses, indicating impaired sinus drainage and ventilation, which may increase the risk of bacterial sinusitis. 7 We have earlier shown that subjects with allergic rhinitis and susceptibility to recurrent sinusitis have impaired sinus functioning during viral colds.…”
mentioning
confidence: 99%
“…In contrast to this study, Carenfelt and Lundberg studied pO 2 , pCO 2 and pH in purulent and non-purulent secretions from human subjects and found that mean pO 2 and pH levels were lower and pCO 2 levels higher in purulent nasal secretions when compared to nonpurulent secretions [11]. To observe the relation between ostial obstruction and maxillary sinus CO 2 level, Ganjian et al [12] analyzed a similar hypothesis in a rabbit model by blocking the maxillary sinus ostium and comparing maxillary gas composition with a control group. Their results showed that blocking the maxillary sinus ostium leads to significant increase in mean CO 2 levels when compared with the control group (7 vs. 3.58%) and they concluded that ostial occlusion causes an increase in CO 2 concentration in the maxillary sinus.…”
Section: Discussionmentioning
confidence: 63%
“…This means that the use of septoplasty alone or combined with FESS in treatment of patients with CRS and deviated nasal septum gives the same outcome. Ganjian et al 1999 have established independent models of nasal obstruction and ostial occlusion in the same animal. Their findings suggested that integrity of nasal airflow seemed to have a significant effect on the maintenance of the aerobic antral environment, essential to the maintenance of normal sinus function [12].…”
Section: Discussionmentioning
confidence: 99%
“…Ganjian et al 1999 have established independent models of nasal obstruction and ostial occlusion in the same animal. Their findings suggested that integrity of nasal airflow seemed to have a significant effect on the maintenance of the aerobic antral environment, essential to the maintenance of normal sinus function [12]. Sarna et al 2002 found that severe septal deviation had been noted as a contributing factor for sinusitis [13].…”
Section: Discussionmentioning
confidence: 99%